« Villes nouvelles » et urbanités émergentes dans les périphéries de Constantine et Marrakech - Jean-Marie Ballout (L’Année du Maghreb)
Since 2000, the outskirts of major North African cities have become the stage of many urban developments, undertaken with a project approach. These major projects were subjected to exhaustive research particularly regarding their political and institutional dimensions. However, their actual socio-spatial effects have not yet been fully disclosed.The purpose of this article is to contribute to this field of research, and more specifically on the subject of the “social reception” of urban planning projects, in this case: “new towns”. Based on the situation analysis and appraisal of the inhabited space of the “new towns” of Ali Mendjeli and Tamansourt, respectively located in the outskirts of Constantine (Algeria) and Marrakech (Morocco), we endeavored to verify whether or not forms of urbanity were emerging in the re-territorialized areas as a result of these projects. In other words, do the inhabitants of “new towns” perceive their space as a city?